Correlation of Motivation and Agripreneurship Intention of Gen Z - Mahmud, Ernida; Ramli, Fatmawati; Asnur, Wahyuni (JURNAL AGRIBISAINS, 2026)
The purpose of this study was to analyze the significant correlation between motivation and agripreneurship intentions of Gen Z in Lappa Upang Village. The study used a quantitative approach with a survey method. The instrument, a Likert-scale questionnaire, measured respondents’ motivation and intentions. Data were analyzed using a Pearson correlation test. The data were analyzed using statistical software, SPSS. The Pearson correlation analysis yielded a correlation coefficient of 0.833 with a significance level of 0.000. This indicates a very strong, positive, and significant relationship between motivation and agripreneurship intentions of Gen Z in Lappa Upang Village. This means that the higher a person’s motivation, the higher their intention to become an entrepreneur in the agripreneurship sector. Therefore, motivation is a psychological factor that plays a crucial role in driving the interest and readiness of Gen Z in Lappa Upang Village to start a business in the agricultural sector.